Актуалізаційні реченнєві категорії: проблема вибору - Мірченко, Микола Васильович; Mirchenko, Mykola (Східноєвропейський національний університет, 2013)
Окреслено суть зовнішньосинтаксичної спеціалізації речення як комунікативної одиниці. Поставлено проблему категорійного вияву актуалізації як надкатегорійної величини, що модельована в реченні значеннями категорії настанови-модальності, часу та персональності, які забезпечують комунікативне членування речення. The external syntactic specialization of the sentence as a communicative unit is outlined. The problem of categorical and intercategorial disclosure of actualization being a cupercategorical notion , which has modeled the meanings of modality-directive, time and personality category providing the communicative parceling of the sentence is put forward.
Actualisation Sentence Categories: the Problem of Choice
Keywords: актуалізація як надкатегорія; комунікативний регістр; триаспектний характер речення; актуальна парадигма речення; варіювання позиційної структури речення; інтерпозиція; препозиція; постпозиція; асоціативні зв’язки; пластика мелодії слова; колір тональності; the actualization as a supercategory; the communicative key; the three-aspect character of the sentence; the actual paradigm of the sentence; the variation of positional structure of the sentence; the interposition; the preposition; the postposition; associative links; the plasticity of word melody; the colour of tonality